Embarrassment and Shame in People With Parkinson's Disease: A New Tool for Self-Assessment - Fleury, Vanessa; Catalano Chiuvé, Sabina; Forjaz, Maria João; Di Marco, Mariagrazia; Messe, Maria; Debove, Ines; Angulo, Julio; Hariz, Gun-Marie; Burkhard, Pierre R.; Martinez-Martin, Pablo; Rodriguez-Blazquez, Carmen; Krack, Paul (Frontiers in Neurology, 2020)
Shame and embarrassment related to Parkinson’s disease (PD) are rarely addressed in clinical practice nor studied in neuroscience research, partly because no specific tool exists to detect them in PD. Objective To develop a self-applied assessment tool of shame and embarrassment specifically related to PD or its treatment, to promptly identify the presence and severity of these two emotions in PD. Methods Identification and selection of items of interest were obtained from the collection of PD patients’ opinions during support groups and interviews. Several further items were added following a literature review. Subsequently, a two-phase pilot study was performed for identification of ambiguous items and omissions, and to obtain preliminary data on acceptability, reliability, validity and relevance of the new scale (SPARK). Results A total of 105 PD patients were enrolled in the study. Embarrassment was reported in 85% of patients, while shame was present in 26%. Fifteen percent of patients did not described any shame or embarrassment. On average, the intensity of these two emotions was low with a marked floor effect in SPARK items and subscales. However, SPARK total score inter-individual variability was important (range 1-84 out of 99). Acceptability and quality of data were satisfactory with no floor or ceiling effects (2.9% each) or missing data. Internal consistency (Cronbach’s alpha) was 0.94 for total score and 0.73-0.87 for subscales. The scale correlated ≥0.60 with instruments measuring related constructs. Content validity was satisfactory. SPARK total score strongly correlated with impaired health-related quality of life (rS=0.81), the propensity to feel embarrassed or ashamed (rS=0.68 and 0.66, respectively), and with anxiety (rS=0.72) and depression (rS=0.63) levels. Moderate to high correlations were observed between SPARK total score and apathy (rS=0.46) and a more pronounced personality trait directed towards harm avoidance (rS=0.46). No significant differences in SPARK scores were found by sex, education level, PD duration, Hoehn and Yahr stages or PD phenotype. Conclusion Preliminary analysis of psychometric properties suggests that SPARK is an acceptable, reliable and valid instrument for assessing shame and embarrassment in PD. SPARK could help healthcare professionals to identify the problem of shame and embarrassment affecting PD patients.